Gambaran Pola Makan dan Aktivitas Penderita Diabetes Mellitus Tipe 2 di Rumah Sakit Daerah Kalisat Jember - Firdaus Maulana; Mad Zaini (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Background: Type 2 Diabetes Mellitus is a chronic metabolic disease characterized by elevated blood glucose levels due to insulin resistance and impaired insulin secretion. One of the influencing factors for this condition is lifestyle, particularly dietary patterns and physical activity. Objective: This study aims to describe the dietary patterns and physical activities of Type 2 Diabetes Mellitus patients at Kalisat Regional Hospital (RSD), Jember. Method: The research design used is a case study involving two patients diagnosed with Type 2 Diabetes Mellitus. Data were collected through interviews, observations, and documentation studies, and analyzed using nursing care stages. Results: The study found that both patients consumed high amounts of simple carbohydrates such as sugar, sweet cakes, and noodles, exceeding the normal daily intake limits. Physical activity was minimal, limited to light household chores like cleaning and short-distance walking. Conclusion: Both patients were diagnosed with ineffective health management. Nursing interventions focused on behavioral health education to improve patients’ knowledge and motivation in managing Diabetes Mellitus independently.